2021
DOI: 10.1177/0260106020983800
|View full text |Cite
|
Sign up to set email alerts
|

Pre-competition body mass loss characteristics of Brazilian jiu-jitsu competitors in the United Kingdom

Abstract: Background: Brazilian jiu-jitsu (BJJ) is a grappling-based combat sport in which competitors engage in pre-competition acute ‘weight’ loss (AWL) and rapid ‘weight’ loss (RWL) to achieve the body mass (BM) required for their desired division. AWL/RWL practices of UK BJJ competitors have not previously been reported. Aim: Our aim in this study was to determine the prevalence, magnitude and stakeholder influences of AWL and RWL amongst BJJ participants in the United Kingdom (UK). A secondary aim was to explore wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…To assess the history of rapid weight loss methods, the Rapid Weight Loss Questionnaire (RWLQ) was applied , adapted to BJJ (White & Kirk, 2021). In addition, a food record of the previous 24 hours was applied to limit the participation of athletes who used medications or supplements that could interfere with hydration status.…”
Section: Questionnairesmentioning
confidence: 99%
“…To assess the history of rapid weight loss methods, the Rapid Weight Loss Questionnaire (RWLQ) was applied , adapted to BJJ (White & Kirk, 2021). In addition, a food record of the previous 24 hours was applied to limit the participation of athletes who used medications or supplements that could interfere with hydration status.…”
Section: Questionnairesmentioning
confidence: 99%
“…Considerable and rapid weight fluctuations in combat-sport athletes have frequently been reported in the literature [ 11 , 12 , 13 ], and many of the techniques are harmful and life-threatening [ 12 , 14 ]. Research on the weight-regulation practices within these sports are concerned about the potential negative effects on physical performance and health due to the long-term effects from repeated weight fluctuations or prolonged periods of low energy availability (LEA), which also increases the risk of eating disorders (EDs) [ 14 , 15 , 16 ]. While some argue that female combat sport athletes are more prone to these negative health impairments compared to males [ 16 ], most studies are limited by few included females [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the weight-regulation practices within these sports are concerned about the potential negative effects on physical performance and health due to the long-term effects from repeated weight fluctuations or prolonged periods of low energy availability (LEA), which also increases the risk of eating disorders (EDs) [ 14 , 15 , 16 ]. While some argue that female combat sport athletes are more prone to these negative health impairments compared to males [ 16 ], most studies are limited by few included females [ 15 ]. Importantly, it has been shown that persons with high level of body appreciation (i.e., “accepting, holding favorable opinions toward, and respecting the body, while also rejecting media-promoted appearance ideals”) are less prone to body figure idealization and the negative mental health effects from LEA [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although still in its infancy, the BJJ research literature has grown substantially over the past few years across multiple domains, such as the psychosocial (Bennett & Dressler, 2020;Mickelsson, 2021;, nutritional (Verli et al, 2021;White & Kirk, 2021), anthropometric (de Paula Lima et al, 2017Øvretveit, 2018b), physiological (Belo et al, 2020;Øvretveit, 2019), and technical-tactical Coswig et al, 2018b). Due to the paucity of research in competitive BJJ, little is known about the performance characteristics of different events, styles, and skill levels.…”
Section: Introductionmentioning
confidence: 99%